Pelaksanaan pembelajaran daring berbantuan video youtube siswa kelas 3 SD - Khofifah Indar Parawansa (ARKA INSTITUTE, 2022)
In learning mathematics, it is very conventional, which still use s guidebooks and worksheets so that it makes students look bored when learning mathematics takes place. During the current pandemic, the learning process uses technology to streamline the learning process and facilitating the learning process. In today's digital era, the learning process uses very advanced and innovative media. Researchers use youtube videos as learning media in weight unit material using songs. The purpose of this study is to determine the performance of video-assisted learning in the YouTube for grade 3 Elementary School. This study uses a qualitative method described with direct observe andtechnical interview . the result of this research in the implementation of student learning were very enthusiastic when the video was shown and students were active in the learning proces. So the learning process assisted by YouTube videos is very useful for the student process of learning weight unit material.